Palliative Management of Nonoperative Femoral Neck Fractures With Continuous Peripheral Indwelling Catheters: Case–Control Series. (6th March 2019) - Rashidifard, Christopher H.; Romeo, Nicholas; Richardson, Mark; Muccino, Paul; DiPasquale, Thomas; Bush, Chelsea M.
Introduction: This case–control study evaluates the success of indwelling pain catheters in nonoperatively treated femoral neck fractures (FNFs) for end-of-life pain management. Methods: Patients older than 65 years with nonoperatively treated FNFs were retrospectively identified at a level 1 trauma center between March 2012 and September 2015. Twenty-three received indwelling continuous peripheral pain catheters (experimental) and 10 received traditional pain control modalities (control). Pain scores 24 hours before/after pain management interventions, ambulation status at admission and discharge, mortality at 30 days/1 year, and length of hospital stay (LOS) were compared between treatment groups. Results: The experimental and control groups were similar with respect to demographics, differing only in pre-fracture ambulatory status ( P = .03). The 30-day mortality was 52% versus 50% (odds ratio, OR: 1.1 [95% confidence interval, CI: 0.25-4.82], P = .99) and 1-year mortality was 87% versus 80% (OR: 1.67 [95% CI: 0.23-11.9], P = .63) for experimental and control groups, respectively. The LOS did not statistically significantly differ for experimental and control groups (5.3 ± 3.56 days vs 3.8 ± 1.81 days, P = .15), respectively. The experimental group experienced twice the improvement in ambulation status (1.0 ± 0.56 vs 0.5 ± 0.71, P = 0.03) and greater improvement in pain scores (4.5 ± 2.19 vs 1.2 ± 2.72, P = .002). Discussion: Operative management of FNFs may not be indicated in patients with advanced age and comorbidities. Regardless, these patients require pain palliation and early mobilization while minimizing hospital LOS and opiate consumption. Conclusion: This case–control study demonstrates significant improvement in both pain level and ambulatory status for patients treated with indwelling continuous peripheral catheters. Future studies should further evaluate with a larger sample size; however, this study provides an excellent launching point for palliative management of this complex population.